1992
DOI: 10.1103/physrevlett.69.2106
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic-field effects inNbSe3

Abstract: We have performed NMR studies on an aligned, multicrystalline NbSe3 sample at various temperatures. We find conclusive evidence of field-induced Fermi-surface changes at low temperatures, and associate these changes with charge-density-wave (CDW) enhancement mainly localized on the yellow crystallographic site, contrary to expectations, since the low-temperature CDW is mainly localized on the orange site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The measurements were taken using a 9-T home-built pulse NMR spectrometer described elsewhere 12 line shapes were obtained from spin echo fast Fourier transforms using a composite-pulse sequence. Wide-line satellite spectra were mapped out by spin echo integration.…”
Section: Methodsmentioning
confidence: 99%
“…The measurements were taken using a 9-T home-built pulse NMR spectrometer described elsewhere 12 line shapes were obtained from spin echo fast Fourier transforms using a composite-pulse sequence. Wide-line satellite spectra were mapped out by spin echo integration.…”
Section: Methodsmentioning
confidence: 99%
“…18(a) reveals a new ordered state below T P 1 . The most obvious reason for this is a lattice distortion coupled with CDW formation, as observed in NbSe 3 [50].…”
Section: The Ultra High-tp Cdw: Indications Of a Peierls Transitmentioning
confidence: 99%
“…This was confirmed by Y.T. Tseng et al 21 who observed pronounced effect of strain on the resistance and thermopower of NbSe 3 below 59 K. Jianhui et al 22 have conducted NMR experiments to study the density of states on the different chains in NbSe 3 . Although magnetic fields effects on the ohmic regime, below E T , are much more pronounced below the second transition than below T p1 , their results show that most of the changes in FS is due to changes in density of states on the chain associated with the upper CDW rather than the lower CDW.…”
Section: Discussionmentioning
confidence: 62%